Understanding of Islamic banking financial management in the context of global economic competition - Suyanto, Suyanto; Lestari, Novi Puji; Yulianti, Eka Budi; Yusroni, Nanang; Chadhiq, Umar (Linguistics and Culture Review, 2021)
The authors believe that understanding Islamic banking financial governance at a globally competitive level is an exciting issue in global economic studies. We have carried out the completeness of the data and the discussion from various sources of information and economic data. Furthermore, our understanding efforts were made to find solutions in answering questions and problems in the context of this study by involving a comprehensive study of economics review, involving a system of data analysis, evaluation, and in-depth conclusion drawing. We carry out this study is in a qualitative type of study relying on secondary data in the form of evidence from previous studies, which we consider valid and updated in response to the problems and questions of this study. Based on the existing data supported by the evidence of previous findings, we found that Islamic banking financial governance in the context of a globally competitive economy is an exciting issue for the parties because the world today is questioned by the failure of the conventional capitalist economy in contributing solutions to the world community. Other findings are very relevant to be discussed and become an essential theme in competitive economics, especially Islamic economics.